Analysis of Households Prosperity of Mango Farmers in Situbondo Regency - Puryantoro; Andina Mayangsari (Publisher Cv. Inara, 2020)
Farmers' household income is an indicator of the level of prosperity by looking at the amount of expenses and family expenses. Mango production, which has increased every year, needs to be assessed according to the level of household poverty. The purpose of this study was to determine the household level of mango farmers in Situbondo Regency. The research location was determined purposively in the Makmur Jaya I Farmers Group, Jangkar District, Situbondo Regency. Population and sample with saturated sampling technique with a population as well as a sample of 25 respondents. Data were collected through primary data (direct interviews using a questionnaire) and secondary data from related agencies and literature related to this study. The data were analyzed by using quantitative descriptive analysis which was measured using Sajogyo's poverty theory. The prosperity level of the members of the Makmur Jaya I Farmer Group is in the decent living category of 64% and the moderate category of 36%. None of the mango farmers in this group are below the poverty line.